Development of fruit-flavored papaya (Carica Papaya L.) based sheets - Wong, Judy Q.
Fruit-flavored papaya sheets were made from Pasteurized papaya puree that was flavor-enhanced with lemon or orange flavors, then dried in a cabinet drier. Determination of the best SS/TA blend of fruit paste was then done. Both objective and sensory evaluations were performed and the two best SS/TA blend of fruit pastes were selected. This was then dried at 160-180°F until there was no change in weight of the product. Sensory evaluations of the fruit sheets indicate that the SS/TA blend of 20°Bx-0.20%TA was the most acceptable. This was then flavor-enhanced by the addition of either orange or lemon to the pastes, at varying levels. A concentration of 0.20% w/w was found to be the best flavor level. The sorption isotherm curves of the products were then determined. The curves were typically sigmoidal in shape. And at the region between the %RH values of 8.5 to 70.4, the product was considered to be the most stable.